2022
DOI: 10.1080/21655979.2022.2063652
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin inhibits the activation of lung fibroblasts and pulmonary fibrosis by regulating the nuclear factor kappa B (NF-κB) pathway

Abstract: Idiopathic pulmonary fibrosis (IPF) is a common pulmonary interstitial disease with a high mortality rate. Adiponectin (APN) is reportedly an effective therapy for fibrosis-related diseases. This study aimed to investigate the potential effects of APN on IPF. Male BALB/c mice were injected with bleomycin (BLM) and treated with different doses of APN (0.1, 0.25, and 0.5 mg/kg). The body weights of the mice were recorded. Immunohistochemical, hematoxylin and eosin, and Masson staining were performed to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 50 publications
(56 reference statements)
2
5
0
Order By: Relevance
“…Decreased serum IL-6 and TNF-α expression within the retinal tissue of adiponectin-treated diabetic retinopathy group goes in line with Wang et al [24] who found that adiponectin is effective in inhibiting inflammation, by inhibition of many cytokines (TNFα, IL-6, IL-1β, and IL-18) through inhibition of the NF-κB signaling inflammatory pathway. Adiponectin increases activity of anti-inflammatory factors e.g., IL-10.…”
Section: Serum Insulinsupporting
confidence: 84%
“…Decreased serum IL-6 and TNF-α expression within the retinal tissue of adiponectin-treated diabetic retinopathy group goes in line with Wang et al [24] who found that adiponectin is effective in inhibiting inflammation, by inhibition of many cytokines (TNFα, IL-6, IL-1β, and IL-18) through inhibition of the NF-κB signaling inflammatory pathway. Adiponectin increases activity of anti-inflammatory factors e.g., IL-10.…”
Section: Serum Insulinsupporting
confidence: 84%
“…Nonetheless, experimental research has demonstrated that adiponectin can suppress the expression of alpha-smooth muscle actin (α-SMA), type I collagen, and pro-inflammatory cytokines [ 25 26 ]. Adiponectin has been proposed as a potential therapeutic agent for fibrosis-associated pathologies, its antifibrotic properties potentially mediated through the inhibition of the nuclear factor-kappa B (NF-κB) signaling pathway [ 27 ]. Another study found that adiponectin mitigated paraquat-induced pulmonary fibrosis in a dose-responsive manner by inhibiting the activation of lung fibroblasts [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The anti-fibrotic effects are mediated through the altered signaling of various pathways such as AMPK, PPAR, and TGF-β1/Smad, inhibiting the differentiation of fibroblasts to myofibroblasts and reducing the production as well as the deposition of extracellular matrix. Numerous studies have investigated its mechanism of action in fibrotic diseases of the kidneys (Jing et al, 2020;Zhao D. et al, 2021), liver (Dong et al, 2015;Udomsinprasert et al, 2018), heart (Fujita et al, 2008;Qi et al, 2014), lungs (Kökény et al, 2021;Wang et al, 2022), and skin (Wang et al, 2023), among other organs and systems, confirming its protective effects. Adiponectin was found to be capable of ameliorating tubulointerstitial fibrosis and suppressing angiotensin II-induced secretion of TGF-β1 and fibronectin in human renal mesangial cells, thereby reducing extracellular matrix synthesis (Tan et al, 2015).…”
Section: Fibrogenesismentioning
confidence: 95%
“…Adiponectin was found to be capable of ameliorating tubulointerstitial fibrosis and suppressing angiotensin II-induced secretion of TGF-β1 and fibronectin in human renal mesangial cells, thereby reducing extracellular matrix synthesis ( Tan et al, 2015 ). Additionally, α-SMA expression was shown to be downregulated by adiponectin in the renal cortex of mice with progressive renal injury induced by the administration of deoxycorticosterone acetate and angiotensin II, as well as in the lung tissues of mice with bleomycin-induced idiopathic pulmonary fibrosis ( Tian et al, 2018 ; Wang et al, 2022 ). Another showed that the administration of the AdipoR agonists JT002, JT003, and JT004 significantly reduced the protein expression level of α-SMA in hepatic stellate cells and slowed the progression of hepatic fibrosis in mice ( Xu et al, 2020 ).…”
Section: Possible Associations Of Adiponectin With the Pathogenesis O...mentioning
confidence: 99%